2021
DOI: 10.3390/horticulturae7030056
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Glucosinolates and Anthocyanins in Kale Leaves Grown in a Plant Factory Using Spectral Reflectance

Abstract: The spectral reflectance technique for the quantification of the functional components was applied in different studies for different crops, but related research on kale leaves is limited. This study was conducted to estimate the glucosinolate and anthocyanin components of kale leaves cultivated in a plant factory based on diffuse reflectance spectroscopy through regression methods. Kale was grown in a plant factory under different treatments. After specific periods of transplantation, leaf samples were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…The annual production of TPC and TFC in plant factories could be estimated using the content per plant at various growth stages without neighboring shading, which could determine the optimal harvest time ( Yoon et al, 2019 ). Chowdhury et al (2021) reported that health-promoting components, specifically glucosinolates and anthocyanin, in kale grown in a plant factory can be estimated through spectral reflectance. Similar to these studies, the annual production of UV-B-induced bioactive compounds can be estimated through UV-B radiation interception analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The annual production of TPC and TFC in plant factories could be estimated using the content per plant at various growth stages without neighboring shading, which could determine the optimal harvest time ( Yoon et al, 2019 ). Chowdhury et al (2021) reported that health-promoting components, specifically glucosinolates and anthocyanin, in kale grown in a plant factory can be estimated through spectral reflectance. Similar to these studies, the annual production of UV-B-induced bioactive compounds can be estimated through UV-B radiation interception analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The best correlation is registered in the case of area A# 9 (695 nm), for which the values of R 2 were in the range of 0.9905 to 0.9977, the values of ER(%) were in the range of 3.0616–5.1745% and the predictive power of the model ranged from 5.37% to 8.31%. The literature indicates the presence of anthocyanins around 627 nm [ 39 ], but the model did not assign a compound to the A#6, probably due to its low values of the areas associated with the Gaussian distributions ( Table 4 ). The concentration of protocatechuic acid significantly correlates ( p < 0.00007) with the area A#2 assigned to the wavelength 429 nm, with values of 0.9970, 5.2081% and 5.5689% for the R 2 , ER (%) and predictive power, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The literature indicates the presence of anthocyanins around 627 nm [ 39 ], but the model did not assign a compound to the A#6, probably due to its low values of the areas associated with the Gaussian distributions ( Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments we have found that high and low GSL content populations differed in their spectral patterns. Following [ 18 ], the absorbance at 425 nm is correlated to total GSL content in Brassica napus , while [ 19 ] found that the spectral reflectance in several bands between 742 and 1000 nm is strongly correlated to individual GSL content in kale ( B. oleracea ). Other differences in the spectral reflectance between populations with contrasting GSL content reflect differences in their vigor, photosynthesis, or water content.…”
Section: Discussionmentioning
confidence: 99%